2016
DOI: 10.1039/c6sm00283h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chain flexibility on the properties of DNA hydrogels

Abstract: The effect of chain rigidity on the mechanic properties of DNA hydrogels was studied. Counterintuitively, the hydrogel formed by mainly flexible chains exhibited better stability, stretchability, and much mechanical properties than the hydrogel containing only rigid chains. Calculations showed that the crosslinking ratio in the hydrogel formed by flexible chains was about twice that of the hydrogel formed by rigid chains under the same conditions. We attributed this to the ease of conformational adjustment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 35 publications
(48 reference statements)
2
27
0
Order By: Relevance
“…These rigid and flexible designs were mixed in fractions between 100, 50, 25, and 0% of rigid linkers at approximately 4% w/v DNA content. The respective mixtures were found to have the corresponding storage moduli of 450, 600, 1800 and 1800 Pa at frequencies between 0.1-10 Hz and gelling temperatures of 40.1, 43.6, 49.4, and 48.7 • C [65]. This example as well demonstrated counterintuitive results where a greater fraction of flexible linkers increased the storage moduli, which was due to an increased number of hybridized crosslinks with the flexible linkers.…”
Section: Nanostructuredmentioning
confidence: 78%
See 2 more Smart Citations
“…These rigid and flexible designs were mixed in fractions between 100, 50, 25, and 0% of rigid linkers at approximately 4% w/v DNA content. The respective mixtures were found to have the corresponding storage moduli of 450, 600, 1800 and 1800 Pa at frequencies between 0.1-10 Hz and gelling temperatures of 40.1, 43.6, 49.4, and 48.7 • C [65]. This example as well demonstrated counterintuitive results where a greater fraction of flexible linkers increased the storage moduli, which was due to an increased number of hybridized crosslinks with the flexible linkers.…”
Section: Nanostructuredmentioning
confidence: 78%
“…This approach yielded counterintuitive results where an increase in valency and hybridization interaction yielded lower storage moduli, which demonstrates the need to consider the availability of binding sites in nanostructured designs. Pan et al conducted an alternative study of linear self-assembling DNA hydrogels which further supports this need for flexibility in the internal structure to enhance macroscopic stiffness [65]. Specifically, 2-3 short DNA strands were designed to hybridize sequentially with one strand designed with a short 10 nt sticky overhang that could hybridize to another long tiled dsDNA strand with a self-complementary overhang.…”
Section: Nanostructuredmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, local inhomogeneities with well-defined nanopores and mechanical properties may be built into the network, as different DNA blocks can be made to hybridize at different temperatures ( 34 ). Indeed, recent shear rheological studies on macroscopic samples ( 3 , 35 , 36 ), here referred to as bulk rheological studies, showed that the specific structure and connectivity of DNA nanostars have a strong influence on their macroscopic mechanical response. However, these low-frequency measurements only describe the systems macroscopic, long-time viscoelastic response and cannot describe how more local relaxation times change as the system goes through the melting transition.…”
mentioning
confidence: 99%
“…Here, we present microrheology studies using diffusing wave spectroscopy (DWS) ( 37 , 38 ) to study the equilibrium elastic and viscous moduli of our DNA gels over a much larger frequency range than that available in bulk rheology ( 39 42 ). In particular, using sealed sample chambers allowed us to perform these measurements over a large temperature range without fear of changes in the samples due to evaporation, which is problematic in bulk rheology ( 35 , 43 ). We show that DWS enables us to link the system’s characteristic binding–unbinding processes with the local and global viscoelastic properties of the gel over a temperature range that covers the full melting region between the DNA nanostars.…”
mentioning
confidence: 99%